Perbandingan Kuat Tekan Paving Blok Berbahan Slag Nikel dengan Penambahan Berbagai Jenis Limbah Plastik - Husein, Laode Muhamad Syawal; Gunawan, Yuspian; Kadir, Abd (Teknik Mesin Universitas Halu Oleo, 2020)
Indonesia's economic development is currently heavily dependent on the industrial sector which continues to experience rapid development. One of the growing industrial areas is the construction industry, especially infrastructure and property development that requires materials such as block paving. The purpose of this research is to find out the comparison of strong press paving blocks with the addition of nickel slag and plastic cacahan (PET, HDPE, LDPE and PP). This research uses conventional (manual) randomized methods. The results of this study showed that the influence of the addition of nickel slag and plastic cacahan in the manufacture of paving blocks against strong press can be concluded that the addition of nickel and plastic slag with strong characteristics can increase the strength of paving block press. The highest average press strength values were in Sample C samples, with mixed variations (cement 25%, coarse aggregate 5%, slag 25%, fine aggregate 5% and HDPE plastic cacahan 40%). has a press force of 155 kg/cm2 with a quality of C based on SNI 03-0691-1996. The lowest press test results were found in sample E (cement 25%, coarse aggregate 5%, slag 25%, fine aggregate 5% and plastic cacahan PP 40%) with a press test value of 87.5 kg/cm2 with a quality of D based on SNI 03-0691-1996. Keywords: Paving block, Plastic Type, Strong Press